A bio-based hydrolysis catalyst for the transesterification of triglycerides. (September 2021) - Al-Mashhadani, Husam A.M.; Mallawarachchi, Samavath; Wang, Haoqi; Fernando, Sandun
Abstract: Lipase is an environmentally friendly catalyst that can be used in biodiesel production. However, lipase is expensive, has shorter shelf life, and cannot withstand harsh reaction conditions. This study shows that an amino acid triad, L-histidine, l -serine, and L-aspartic acid, could successfully catalyze the hydrolysis reaction. Both lipase and the amino acid triad showed similar activity in the hydrolysis of triolein substrate. For soybean oil, lipase performed better at high substrate concentrations. In terms of glycerol yield, lipase and amino acid triads performed equally at low substrate concentrations, while lipase performed better at high substrate concentrations. Both Vmax and Km of the triad were smaller than those of lipase. This work proves that the free amino acids arrange around the substrate such that they can synergistically catalyze the hydrolysis reaction while also paves the way to the bottom-up design of the active site leading to the development of synthetic lipases. Graphical abstract: Unlabelled Image Highlights: Amino acid triad L-histidine, l -serine, L-aspartic acid can hydrolyze triglycerides. For triolein, lipase and triad gave similar catalytic activity and glycerol yield. For soybean oil, the triad performed better at lower substrate concentrations. Both Vmax and Km of the triad were smaller than those of lipase.